2007
DOI: 10.1002/ajmg.c.30130
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal and postnatal lung and vascular anatomic and functional studies in congenital diaphragmatic hernia: Implications for clinical management

Abstract: Congenital diaphragmatic hernia is characterized by fetal and neonatal lung hypoplasia as well as vascular hypoplasia. Antenatal imaging studies have been performed that attempt to quantify the degree of hypoplasia and its impact on infant prognosis. Prenatal and perinatal growth of the lung and vasculature are interdependent and their continued coordinated growth is critical for survival after birth in this patient population. Lung protection strategies appear to improve survival in newborns with diaphragmati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 122 publications
0
20
0
Order By: Relevance
“…The technique consistently used and reported at UCSF uses the aorta and lateral rib as landmarks for the lateral measurement, with the orthogonal anterior-posterior (AP) diameter measured from the cardiac atria to the posterior rib, then dividing by the head circumference. 15,26 All analyses were done first including scans from 22 through 27 weeks’ GA 10,11 and then expanding to 20 to 29 weeks’ GA. As results did not differ when using these two inclusion criteria, data from the broader range of ages are presented to increase the information provided in our analyses. Liver position was gathered from fetal ultrasound reports, and verified by operative report from CDH repair, if surgery was performed.…”
Section: Methodsmentioning
confidence: 99%
“…The technique consistently used and reported at UCSF uses the aorta and lateral rib as landmarks for the lateral measurement, with the orthogonal anterior-posterior (AP) diameter measured from the cardiac atria to the posterior rib, then dividing by the head circumference. 15,26 All analyses were done first including scans from 22 through 27 weeks’ GA 10,11 and then expanding to 20 to 29 weeks’ GA. As results did not differ when using these two inclusion criteria, data from the broader range of ages are presented to increase the information provided in our analyses. Liver position was gathered from fetal ultrasound reports, and verified by operative report from CDH repair, if surgery was performed.…”
Section: Methodsmentioning
confidence: 99%
“…Prompted by the observation that congenital laryngeal atresia was associated with enlarged hyperplastic lungs, Wilson et al [92] showed that rapid pulmonary growth could be obtained by occluding the fetal trachea of the hypoplastic lung by, preventing the normal efflux of intraluminal lung liquid [93,94]. FETO accelerates fetal lung growth [95], with increased alveolar and capillary growth, and remodelling of pulmonary arterioles [93,94].…”
Section: Prenatal Treatmentmentioning
confidence: 99%
“…Pulmonary vascular density is reduced, vessel walls overly muscularized, and vasoreactivity impaired, leading to marked elevation of pulmonary vascular resistance (PVR) (15). The resultant pulmonary hypertension (PH) and secondary cardiac dysfunction are both strongly associated with acute and longterm morbidity and mortality in CDH (10,24,39).…”
mentioning
confidence: 99%